Characterization of size-sorted particulated matter collected on solid substrates by laser-ionization mass spectrometry and laser-induced breakdown spectrometry - Medina, Samara; Vadillo-Pérez, José Miguel; Laserna-Vázquez, José Javier (My University, 2016)
Resumen de trabajos realizados mediante excitación láser de material particulado y su posterior análisis mediante espectroscopía óptica de emisión o ionización.
Keywords: Espectroscopía de láser; Espectroscopía de plasma inducido por láser; Particulated matter; Laser ionization; Laser plasmas